Predicting Marital Burnout Based on the Severity of Early Maladaptive Schemas and Criteria for Mate Selection in Female Teachers - Dehghani , Maryam; Ashayeri , Shabnam; Aramideh , Ameneh; Saremi, Azadeh; Poorhashem sarhammami, Atena (Psychology of Woman Journal, 2023)
Objective: The study aims to investigate the relationship between caregiving burden, social support, and psychological distress among mothers of children with autism spectrum disorder (ASD). It specifically examines the mediating role of social support in the linkage between caregiving burden and psychological distress. Methods and Materials: The study employed a descriptive correlational method. The target population comprised all female teachers in Shiraz city in 2021. A purposive sample of 200 teachers was selected. Data were collected using the Young Schema Questionnaire (YSQ), Rafahi and colleagues’ Mate Selection Criteria Questionnaire (2008), and the Pines Marital Burnout Scale (1996). The collected data were analyzed using Pearson correlation coefficients and multivariate regression in SPSS-24 software. Findings: The results indicated that mate selection criteria with a beta coefficient of -0.13, positive perfectionism with a beta coefficient of 0.31, and negative perfectionism with a beta coefficient of -0.19 significantly predicted marital burnout. Additionally, schemas in the domains of rejection and disconnection (beta = 0.59), impaired autonomy and performance (beta = 0.26), impaired limits (beta = 0.19), and other-directedness (beta = 0.20) were significant predictors of marital burnout in female teachers. Conclusion: The study concludes that both early maladaptive schemas and mate selection criteria are significant predictors of marital burnout among female teachers. The findings suggest that interventions targeting these schemas and criteria can be beneficial in addressing marital burnout.